An analysis of the transformative potential of Australia's national food policies and policy actions to promote healthy and sustainable food systems - Patricia Ribeiro de Melo; Phillip Baker; Priscila Pereira Machado; Elly Howse; Scott Slater; Mark Lawrence (Cambridge University Press, 2024)
Abstract Objective: Despite commitment by many countries to promote food system transformation, Australia has yet to adopt a national food policy. This study aimed to evaluate Australian Federal Government's (AFG) food policies and policy actions potential to promote healthy and sustainable food systems. Design: This study is a desk-based policy mapping followed by a theoretically guided evaluation of policy actions. This involved three steps: (1) identification of government departments and agencies that could influence Australia's food system; (2) identification of food policies and policy actions within these departments and (3) use of a conceptual framework to evaluate policy actions' potential of changing the food system as adjust (first-order change), reform (second-order change) or transform (third-order change). Setting: Australia. Participants: None. Results: Twenty-four food policies and sixty-two policy actions were identified across eight AFG departments and the Food Regulation System and evaluated based on the order of change they represented. Most policies were led by individual departments, reflecting the absence of a joined-up approach to food policy in Australia. Most policy actions (n 25/ 56·5 %) were evaluated as having adjust potential, whereas no transformative policy action was identified. Conclusions: These findings suggest that Australia is likely to proceed incrementally towards achieving food system change through adjustments and reforms but lacking transformative impact. To promote transformative change, all three orders of change must be strategically implemented in a coherent and coordinated matter. A comprehensive national food policy and a national coordinating body are needed to ensure a cohesive approach to policy.